THE ROLES OF TEACHER'S FEEDBACK INASSISTING STUDENTS' ENGLISH LANGUAGELEARNING COMPETENCE:A Descriptive Study of EFL Teacher and Students in SMAN 24 Bandung - Dani Hamdani, - (2008)
The study is aimed to explore a teacher's perceptions of feedback, to investigate the types of feedback the teacher usually gives, and to discover the roles of the teacher's feedback in assisting students1 learning improvement. This study uses a qualitative descriptive method in which the data were collected by using classroom observation, questionnaires, and interview to one EFL teacher in SMAN 24 Bandung and her students. The results indicate that the teacher perceived feedback as an input only to motivate the students1 learning; and the teacher still misperceived the categorization of feedback. In the level understanding the teacher still misperceived feedback, even though in the level of practice the teacher gave feedback to the students frequently since she strongly believed that feedback is important for students' learning. Thus, different types of feedback given by the teacher proved to be assisting students' learning at different levels: in encouraging the students to have mistakes alert, exploring the students' underlying concept to the corrections they made.